(untitled) (Cadernos de Sociomuseologia, 2025)
In its short existence as a scientific discipline, museology has managed to overcome numerous challenges to make museums inclusive and democratic spaces. The path to achieving this had its turning point in the 1970s and 1980s with the birth of New Museology. The paradigm shift brought about by its premises placed social function as the essential pillar of any museum institution.In the 21st century, New Museology faces new challenges. Now, under the name of Social Museology, it must address the needs of contemporary societies. The following lines outline the challenges facing New Museology and those that Social Museology must address today: the defence of human rights and democratic values, sustainability, gender violence, social justice, depopulation, decolonisation, etc. Keywords: New Museology, Social Museology, community, territory, democratic values.